Frequency Of Prolonged Qtc in Patients With Decompensated Chronic Liver Disease In A Rural Cohort Of Sindh - Adeel Ahmed; Bushra Rabbani; Muhammad Kamran; Ammarah Saeed; Jameel Ahmed (Journal of Rawalpindi Medical College)
Objective: To determine the frequency of prolonged QTc (corrected QT) interval in patients. With decompensated chronic liver disease (DCLD) in a tertiary care hospital of Gadap town, Sindh.